Production and marketing of safou (Dacryodes edulis) in Cameroon and internationally: market development issues - Awono, A.; Ndoye, O.; Schreckenberg, Kate; Tabuna, H.; Isseri, F.; Temple, L. (2002)
This paper draws together information from three separate projects on the production of Dacryodes edulis (G. Don) H.J. Lam or 'safou' in Cameroon, and its domestic and international trade. The volume of safou fruit commercialised in Cameroon in 1997 was estimated at 11,000 tonnes, equivalent to US$7.5 million. Exports from Central Africa and Nigeria to France, the United Kingdom and Belgium were worth over US$2 million in 1999. A study of nine markets inthe humid forest zone of Cameroon revealed that women dominate the retail trade while men concentrate on wholesale. For both, safou trade is an important long-term livelihood option. Depending on the market and volume traded, weekly marketing margins can be double the minimumm wage. Far from being exploited by traders, producers were found to receive 75% of the consumer price on average. The main constraint to both the domesstic and international trade is the high perishability of safou.